2017
DOI: 10.5301/jbm.5000248
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Vitamin D Receptor (VDR), CYP27B1 and CYP24A1 Genes and the Risk of Colorectal Cancer

Abstract: Dietary habits, lifestyle, and polymorphisms in VDR (ApaI), CYP24A1 (rs6013897, rs158552, rs17217119) and CYP27B1 (rs10877012) were associated with a higher risk of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
(39 reference statements)
2
33
1
1
Order By: Relevance
“…Our data suggest a protective role of the T allele (for TT vs. GT + GG: OR = 2.94; 95% CI 1.77-4.86; p < 0.0001) and the TT genotype (for GT vs. TT: OR = 2.56; 95% CI 1.23-5.32; p = 0.01; for GG vs. TT: OR = 3.20; 95% CI 1.51-6.77; p = 0.002). Contrary to our findings, Vidigal et al (whose study was based in Brazil) indicate that in the male population the presence of T allele increases the risk of CRC by 1.60-fold (p = 0.037), while the presence of GT genotype-by 2.04-fold (p = 0.014) [20]. The MAF in Latin Americans is similar to the MAF in Europeans, but the difference could cause the discrepancies in results between the papers [19].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data suggest a protective role of the T allele (for TT vs. GT + GG: OR = 2.94; 95% CI 1.77-4.86; p < 0.0001) and the TT genotype (for GT vs. TT: OR = 2.56; 95% CI 1.23-5.32; p = 0.01; for GG vs. TT: OR = 3.20; 95% CI 1.51-6.77; p = 0.002). Contrary to our findings, Vidigal et al (whose study was based in Brazil) indicate that in the male population the presence of T allele increases the risk of CRC by 1.60-fold (p = 0.037), while the presence of GT genotype-by 2.04-fold (p = 0.014) [20]. The MAF in Latin Americans is similar to the MAF in Europeans, but the difference could cause the discrepancies in results between the papers [19].…”
Section: Discussioncontrasting
confidence: 99%
“…The MAF in Latin Americans is similar to the MAF in Europeans, but the difference could cause the discrepancies in results between the papers [19]. For males and females, the association of GT+TT vs. GG caused a 2.14-fold greater risk for neoplasia (p = 0.003) [20]. Comparison of GG vs. TT in the whole population: we obtained a 3.20-times (p = 0.002) higher risk of CRC, whereas for Vidigal et al's population the result was not statistically significant (p = 0.412) [20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Vitamin D plays a crucial role in the pathogenesis of colorectal cancer and epidemiological research has put forth evidence that vitamin D plays a protective role against colorectal cancer (50). The role of polymorphisms of VDR and CYP27B2 and CYP24A1, which are involved in the production and suppression of vitamin D, have all been linked to colorectal cancer risk (51 (52). Another study in Japan found an association between common genetic variations in VDR and risk of colorectal cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…показало, что генотип Aa и ассо-циации генотипов aa + Aa ApaI полиморфизма гена VDR повышали риск колоректального рака. BsmI полиморфизм не был ассоциирован с риском данно-го заболевания [28].…”
Section: обзоры литературыunclassified